From fermentation to cancer prevention: The anticancer potential of Kombucha - Opik Taupiqurrohman; Lathifah Puji Hastuti; Dina Oktavia; Belal Omar Al-Najjar; Muhammad Yusuf; Yani Suryani; Shabarni Gaffar (Phytomedicine Plus)
Background: Kombucha is a fermented tea with a distinct sweet and sour taste. It is believed to offer several health benefits, including improved digestion, enhanced immune system, detoxification, and potential anticancer activity, which is thought to be linked to its unique chemical constituents formed during fermentation. Purpose: This article explores how the fermentation process affects the chemical constituents of Kombucha and their potential anticancer activity. Methods: Data was obtained from the Publish or Perish application with the keywords Kombucha, fermented Kombucha, Kombucha on cancer. Then the article is analysed. A total of 97 research articles were retrieved after applying inclusion and exclusion criteria Results: Based on the report, the composition and quantity of chemical constituents in Kombucha are significantly affected by factors such as the fermentation substrate, temperature, and duration. These variables can be optimized to generate novel compounds and enhance the yield of existing ones. The chemical constituents of Kombucha inhibit the proliferation of cancer cells by targeting specific proteins involved in carcinogenesis, such as HIF-1α, VEGF, IL-8, COX-2, as well as caspases-3, -8, and -9, PARP, Bax, Bcl-2, p53, p21, MMP-2, MMP-9 and β-actin. However, comprehending the precise mechanisms governing the interactions between distinct chemical constituents within Kombucha and cancer cells is pivotal for thoroughly grasping its anticancer properties. Conclusion: Kombucha contains chemical constituents that play a role in inhibiting cancer cells. Some of these chemical compounds are glucuronic acid, gluconic acid, d-saccharic acid 1,4-lactone (DSL), acetic acid, ascorbic acid, succinic acid, dimethyl 2-(2‑hydroxy-2-methoxypropylidine) malonate and vitexin with protein carcinogenic protein targets HIF-1α, VEGF, IL-8, COX-2, as well as caspases-3, -8, and -9, PARP, Bax, Bcl-2, p53, p21, MMP-2, MMP-9 and β-actin